EFEKTIVITAS MEDIA PEMBELAJARAN DAN MINAT BELAJAR PENGARUHNYA TERHADAP HASIL BELAJAR AKUNTANSI DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING PADA SISWA KELAS XI SMK NEGERI DAN SWASTA DI JAKARTA TIMUR - Agus Abdillah (Jurnal Pendidikan Ekonomi, 2017)
Abstract The aims of this research was to find the effect of efectifities learning media, learning interest and learning motivation  directly and indirectly  toward learning outcomes of studentsclass  of the economic lesson Senior High School in Bukittinggi. The population of this research were students of economic class on social sciences studies program of 2016, amounting to 782 people. The sample in this research amounted to 90 people. The sampling method was done by using proportionate cluster random sampling. Data collection is done by filling questionaires and documentation of student learning outcomes. Analysis of the data used is path analysis. Data processing is performed with SPSS version 22.0.The results showed that there is significant influence between efectifities learning media to learning interest (1), efectifities learning mediato learning motivation (2), learning interest to learning motivation (3), efectifities learning mediato learning outcomes (4). learninginterest to learningoutcomes (5)andlearning motivation to learningoutcomes (6). Totally, the magnitude of the effect is known 59,08% directly and indirectly, while the remaining 40,92%is influenced by other factors not examined in of this research. Key words: Learning Outcomes , Learning Motivation , Learning Interest and Efectifities Learning Media.